2015
DOI: 10.3233/jad-141173
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements in Alzheimer's Disease

Abstract: A growing body of literature has investigated changes in eye movements as a result of Alzheimer’s disease (AD). When compared to healthy, age-matched controls, patients display a number of remarkable alterations to oculomotor function and viewing behavior. In this article, we review AD-related changes to fundamental eye movements, such as saccades and smooth pursuit motion, in addition to changes to eye movement patterns during more complex tasks like visual search and scene exploration. We discuss the cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 130 publications
7
122
0
Order By: Relevance
“…Consistent with this, a recent review on eye movements in AD concluded that some of the basic oculomotor changes associated with AD are present in MCI and that eye movements may be useful in detecting the early stages of memory impairment (Molitor et al 2015). However, these studies predominantly addressed a single domain of cognitive dysfunction (e.g., episodic memory or executive function), most included an exclusively amnestic MCI population (i.e., aMCI), and none examined these processes during completion of everyday tasks, which are subtly compromised in MCI but have been shown to be strongly associated with conversion to dementia.…”
Section: Eye Movements In Mild Cognitive Impairmentmentioning
confidence: 71%
See 1 more Smart Citation
“…Consistent with this, a recent review on eye movements in AD concluded that some of the basic oculomotor changes associated with AD are present in MCI and that eye movements may be useful in detecting the early stages of memory impairment (Molitor et al 2015). However, these studies predominantly addressed a single domain of cognitive dysfunction (e.g., episodic memory or executive function), most included an exclusively amnestic MCI population (i.e., aMCI), and none examined these processes during completion of everyday tasks, which are subtly compromised in MCI but have been shown to be strongly associated with conversion to dementia.…”
Section: Eye Movements In Mild Cognitive Impairmentmentioning
confidence: 71%
“…We further maintain that the examination of visual behaviors in MCI during everyday task performance is a critical future step in characterizing the changes during this stage that may be most relevant for prognosis and intervention. Findings from studies thus far exploring specific visual behaviors in MCI will be described in this section (see also Molitor et al 2015;Pereira et al 2014). …”
Section: Eye Movements In Mild Cognitive Impairmentmentioning
confidence: 99%
“…In order to verify this hypothesis, eye movements of AD patients have been compared to those of healthy subjects in many studies and effectively, it has been proven that AD patients suffer from changes in oculomotor and pupillary functions [217]. More precisely, changes in saccades, smooth pursuit function and in the pupillary response have been found by some researchers.…”
Section: Eye Dynamicsmentioning
confidence: 99%
“…New findings also show a great potential to increase our understanding of dementia and its impact on linguistic degradation such as loss of vocabulary, syntactic simplification, poor speech content and semantic generalization. Analysis of eye movement is also a relevant research technology to apply, and text reading by people with and without mild cognitive impairment may give a clear ruling on how reading strategies differ between these groups, an area that has so far not been researched to any significant extent in this particular domain (Fernández et al, 2013(Fernández et al, , 2014Molitor et al, 2015). With the help of eye-tracking technology the eye movements of participants are recorded while suitable stimuli is presented (e.g., a short text; cf.…”
mentioning
confidence: 99%
“…For instance, the longer the eye gaze fixation is on a certain word, the more difficult the word is for cognitive processing, therefore the durations of gaze fixations could be used as a proxy for measuring cognitive load (Just & Carpenter, 1980). Molitor et al (2015) provide a recent review on the growing body of literature that investigates changes in eye movements as a result of AD and the alterations to oculomotor function and viewing behavior. …”
mentioning
confidence: 99%